Pemberdayaan Masyarakat Dalam Penggunaan Artificial Intelligence Aktivitas Urban Farming Di Kelurahan Semanan, Provinsi DKI Jakarta - Prakoso, Jatayu Hadi; Bayquni, Bayquni; Yulistiani, Indriati; Katerina Herlin, Aurin; Nadhira, Nadhira; Sahara, Aulia; Alfiansyah, Alfiansyah; Romdoni, Doni; Lie, Steafian (PELITA NUSA TENGGARA, 2026)
This community service program aims to enhance the capacity of residents in Semanan Urban Village to implement Al-based urban farming as a strategy to strengthen food security, digital literacy, and community empowerment. The activities were carried out through stages of socialization, training, technology implementation, mentoring, and evaluation, grounded in development communication and participatory communication approaches. The results indicate that integrating urban farming with Al technologies- such as soil sensors, plant monitoring applications, and automated irrigation systems— successfully improved the community's knowledge and technical skills in managing urban agriculture. Training sessions utilizing instructional communication and hands-on learning effectively increased digital literacy and accelerated the adoption of technological innovations. Continuous mentoring and the establishment of an urban farming community strengthened program sustainability through information exchange, collaboration, and enhanced community ownership of the innovation. Additionally, the production of a short documentary served as an effective audio-visual medium to broaden information dissemination and highlight the role of visual communication in community empowerment. Overall, the program not only improved urban farming productivity but also strengthened communication capacity, social inclusion, and technological independence at the community level. The integration of Al into urban farming proved to be an effective, adaptive, and replicable innovation for other urban areas.